Project-Based Learning in Vocational Education: A Systematic Literature Review on Technological Literacy and Industry Readiness - Deded Darmadi; Waskito; Hasan Maksum (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Project-Based Learning (PjBL) has emerged as a prominent instructional approach in vocational education to bridge the gap between theoretical knowledge and industry demands in the Industry 4.0 era. This systematic literature review examines the implementation of PjBL in vocational education, specifically analyzing its effects on technological literacy and industry readiness outcomes. Unlike previous reviews that focus on general education contexts, this review uniquely emphasizes vocational and technical education, particularly Computer Numerical Control (CNC) learning, and synthesizes evidence on both learning outcomes and implementation barriers. Following PRISMA guidelines, this review analyzed 20 peer-reviewed articles published between 2019-2025 from Scopus, Google Scholar, ERIC, ScienceDirect, and SpringerLink databases. Findings indicate that PjBL positively contributes to improving technological literacy, critical thinking, collaboration, and industry-readiness competencies among vocational students. Project-oriented learning creates more active and experiential learning environments compared to conventional instruction, enhancing students' understanding of industrial systems and problem-solving skills. However, implementation challenges including limited technological facilities, insufficient teacher readiness, and time constraints must be addressed. This review confirms that PjBL holds substantial potential to align vocational education with contemporary industrial demands, while identifying key implementation barriers and specific recommendations for practitioners and policy makers.